Light pollution and warming: consequences for freshwater invertebrate Girardia tigrina - Veiga, Filipa Almeida Casal da (2023)
Human society has entered an era of increasing urbanization, and this persistent increase of people living in cities along with human activities poses great threats to biodiversity. All over the world human population shows a tendency to be near rivers and ponds making freshwater ecosystems more vulnerable to urbanization associated pressures. One of these pressures of urbanization is light pollution, which is caused by the presence of artificial light at night (ALAN). Light is an environmental cue that regulates circadian rhythms and melatonin production; however, ALAN may disrupt circadian rhythms through the suppression of melatonin production. Urban streams are also susceptible to warmer temperatures due the absence of grasslands and increased impervious surfaces (urban heat island), influencing thermal conditions of aquatic organisms. Therefore, it is essential to understand how exposure to ALAN influences thermal tolerance of species. The aim of this work was to evaluate if ALAN alters the thermal tolerance of Girardia tigrina and studying the role of melatonin in mediating such heat tolerance. To determinate the upper thermal limit of G. tigrina, organisms were exposed for fourteen days to different light intensities at night (0, 1 and 10 lx) in the presence and absence of exogenous melatonin (1 μM) and then the critical thermal maximum was estimated. To assess how ALAN and warming influence behaviour endpoints (feeding and locomotion) and regeneration, G. tigrina was subjected to a ten-day exposure of mean higher temperatures (20 and 24°C), ALAN (0, 1 and 10 lx) and exogenous melatonin (0 and 1 μM), in a full factorial design. ALAN reduced the critical thermal maximum of G. tigrina, in a light-intensity dependent manner. Exogenous melatonin tended to ameliorate the effects induced by exposure to ALAN. Planarians locomotor velocity was reduced by ALAN. Regarding regeneration, as expected, the higher temperature (24°C) accelerated the regeneration process and ALAN delayed regeneration in both temperatures Melatonin slightly increased locomotor velocity in higher levels of ALAN and, although melatonin mitigated the effects of ALAN on thermal tolerance of this species, the same was not confirmed for regeneration. Thus, with this work is possible to conclude that ALAN alters G. tigrina thermal tolerance and, observed effects may compromise organisms thermal limits, locomotor velocity and even their ability to reproduce. Since ALAN causes these effects in organisms, it would be necessary to establish strategies to reduce ALAN in order to promote conservation of these freshwater communities. Melatonin proved to be a hormone that regulates artificial light impacts. Finally, and considering the results obtained, it’s important to continue and narrow investigation of light pollution and its combined effects with other stressors (warming, chemical exposure) since is critical to understand ecological consequences of environmental changes in urban aquatic ecosystems.